Pengaruh Social Media Marketing terhadap Repurchase Intention dengan Brand Image Sebagai Mediasi - Gusti Ayu Agung Wulan Pramestya Putri; I Made Jatra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
One of the most demanded categories of cosmetic products is lip cosmetics. However, competition in this industry is getting tougher with the entry of various new companies that offer a variety of products so that the preferences of consumers will continue to change. One of the prominent lip cosmetic companies is the Revlon brand, with its flagship product, the Revlon SuperLustrous Lipstick, which managed to dominate the market and become iconic among Indonesian consumers, but in recent years Revlon lipsticks have experienced fluctuations that tend to decrease on the Top Brand Index and experience a decline in sales in Denpasar City. This study aims to analyze the influence of social media marketing on repurchase intention with brand image as mediation for customers of Revlon lipstick products. This research is a research that uses a quantitative approach in the form of causal associatives. Sugiyono (2019: 65). Based on the results of research analysis, it was found that social media marketing has a positive and significant effect on repurchase intention, social media marketing has a positive and significant effect on brand image, brand image has a positive and significant effect on repurchase intention, and brand image is able to mediate the influence of social media marketing on repurchase intention. Next, brand image partially mediates social media marketing against repurchase intention.